2012
DOI: 10.1161/circep.111.969865
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Late Potentials for 24 Hours Between Brugada Syndrome and Arrhythmogenic Right Ventricular Cardiomyopathy Using a Novel Signal-Averaging System Based on Holter ECG

Abstract: Background— Late potentials (LP) detected with signal-averaged ECGs are known to be useful in identifying patients at risk of Brugada syndrome (BS) and arrhythmogenic right ventricular cardiomyopathy (ARVC). Because the pathophysiology is clearly different between these disorders, we clarified the LP characteristics of these disorders. Methods and Results— This study included 15 BS and 12 ARVC patients and 20 healthy controls. All BS pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 38 publications
0
28
0
1
Order By: Relevance
“…Recent data derived from an ex vivo canine model challenge previous conclusions, attributing LPs to abnormal conduction or structural abnormalities in the RV epicardium; these experiments indicated that LPs in Brugada syndrome may be associated with the development of abnormal repolarization in the RV epicardium that can set the stage for concealed reentry . Interestingly, circadian periodicity has been noted in the presence of LPs; this observation, derived from Holter‐SAECG recordings, was characterized by increased incidence of LPs during the night, likely resulting from enhanced vagal tone . Based on this finding, LPs during nighttime, along with enhanced T‐wave amplitude variability, have been proposed as additional noninvasive risk‐stratification tools .…”
Section: Potential Future Applicationsmentioning
confidence: 88%
See 1 more Smart Citation
“…Recent data derived from an ex vivo canine model challenge previous conclusions, attributing LPs to abnormal conduction or structural abnormalities in the RV epicardium; these experiments indicated that LPs in Brugada syndrome may be associated with the development of abnormal repolarization in the RV epicardium that can set the stage for concealed reentry . Interestingly, circadian periodicity has been noted in the presence of LPs; this observation, derived from Holter‐SAECG recordings, was characterized by increased incidence of LPs during the night, likely resulting from enhanced vagal tone . Based on this finding, LPs during nighttime, along with enhanced T‐wave amplitude variability, have been proposed as additional noninvasive risk‐stratification tools .…”
Section: Potential Future Applicationsmentioning
confidence: 88%
“…52 Interestingly, circadian periodicity has been noted in the presence of LPs; this observation, derived from Holter-SAECG recordings, was characterized by increased incidence of LPs during the night, likely resulting from enhanced vagal tone. 53 Based on this finding, LPs during nighttime, along with enhanced T-wave amplitude variability, have been proposed as additional noninvasive risk-stratification tools. 54 Nonetheless, further research is needed on this subject, prior to the clinical use of SAECG in Brugada syndrome.…”
Section: Brugada Syndromementioning
confidence: 99%
“…Finally, it is also well known that LP have important circadian variability in Brugada syndrome patients, especially in those with documented arrhythmias (Yoshioka et al., ). Furthermore, this circadian variability is absent in ARVC, another arrhythmogenic heart disease characterized by the presence of LP (Abe et al., ). Regarding fQRS, most studies used the definition proposed by Morita (Morita et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this circadian variability is absent in ARVC, another arrhythmogenic heart disease characterized by the presence of LP (Abe et al, 2012). Regarding fQRS, most studies used the definition proposed by Morita (Morita et al, 2008).…”
Section: Methodological Issues With Lp and Fqrs Measurement And Intmentioning
confidence: 99%
“…68 Recently, Abe et al found that fluctuations in LPs on signal-averaged ECG (SAECG) occurred predominantly at night, suggesting that conduction delay and, by inference, the arrhythmogenic substrate are autonomically modulated. 69 Therefore, it is plausible that at night during sleep, when vagal tone is usually increased and associated with the withdrawal of sympathetic activity, the VF substrate is modulated and more susceptible to arrhythmogenesis. Kasanuki et al also showed a sudden increase in vagal activity, as measured by heart rate variability (HRV), just before episodes of VF in a patient with BS.…”
Section: Autonomic Nervous Systemmentioning
confidence: 99%